The Concept of Justice According to Pancasila and Its Relevance to Law Enforcement - Tambunan, Joy Catherine Carina; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Justice is a fundamental goal in the Indonesian legal system, with Pancasila as the philosophical foundation and source of all sources of law (staatsfundamentalnorm). However, there is a significant gap between the ideal of Pancasila justice and the reality of law enforcement, which is considered discriminatory and not fully in favor of human values. This study aims to philosophically examine the concept of justice according to Pancasila and analyze the relevance and challenges of its application in law enforcement practices in Indonesia. Using normative legal research methods with philosophical, legislative, and conceptual approaches, this study finds that justice in Pancasila is holistic, integrative, and substantive, which is inspired by its five principles in an integrated manner: moral-spiritual values (Principle 1), respect for human dignity (Principle 2), strengthening unity (Principle 3), achievement through deliberation (Principle 4), and equitable distribution of welfare (Principle 5). Despite its high normative relevance, its implementation is hampered by various factors, such as the dominance of a rigid legal positivism paradigm, political intervention, corruption, and unequal access to justice. Therefore, a reconstruction of the law enforcement paradigm and systemic reforms focused on internalizing Pancasila values are needed to realize the desired substantive justice.